EVOLUSI JAWARA DI BANTEN (STUDI EVOLUSI DARI BANDIT MENJADI PEJABAT) - Bandiyah, Bandiyah (Jurnal Interaktif, 2010)
Jawara used to a âsantriâ (student at traditional Muslim school), an apprentice of a âkiayiâ (teacher of Islam) who had supernatural and divine power, who fought against the colonial in Banten. Furthermore, they also became bandit because of their bad behavior in which they brought about criminal and violence to the society around them. Later on, they became the sub-culturalism which grow in Banten. Unfortunately, this situation was benefited by Golkar (Labor Class) Party as the mass mobilize machine for the sake of New Order Regime. In the other hand, it gave advantage toward Jawara to experience political realm there so that they could absolutely access entire local sources with their great attempts. When there was the Reformation Era, followed by policies about decentralization and local autonomy which made Banten became new province, it automatically gave opportunity to Jawara having role more active and unhampered in local government of Banten. Having possessed significant role in the Banten province establishment, Jawara recently owns crucial role local government bureaucracy by being a number one person as a governor there. This study is done to reveal âHow did Jawara evolve from being a bandit into local official and control Banten Governance?â To answer such a question, the researcher implements theoretical framework that is theory of social alteration and jawaraâs evolution. Moreover, the researcher employs qualitative method by historic descriptive approach as the research methodology. The method of data collecting is interview technique, documentation study, monitoring, and observation.The findings of this research reveal that Jawara carry out evolution through 2 factors. The first is that the actors (Jawara) change in which they have an ability to do various things, i.e. acceleration in building Jawara interrelation, acceleration through organization training, acceleration in individual competition, heading toward culture and belief principles, participation in Banten Province establishment, and using violence as power instrument. The second is the emergence of structural alteration. This change gives greater opportunity to penetrate into the society and local government so that they can access their power in candidacy as a Vice Governor of Banten at 2001 and afford to consolidate local politic there that ultimately became Governor of Banten in the period of 2006 until 2011. However, this structural alteration succeeds to be a supporter in evaluation process of Jawara. Indeed, the actors ability have definitely the one which can consolidate back his role in Banten. The second of factors interact become power of informality government Jawara, that work in illegal structure expression shadow state.Key words: Jawara, social Evolution, aktor alteration, Structural Change